1957
DOI: 10.1149/1.2428544
|View full text |Cite
|
Sign up to set email alerts
|

Semiconducting Properties of Some Vanadate Glasses

Abstract: Glasses have been made in the systems normalBaO‐V2O5‐P2O5 and Na2O‐normalBaO‐V2O5‐P2O5 with V2O5 contents ranging between 50 and 87 mole%. The glasses were found to be semiconductors, those with the highest V2O5 contents having a specific conductivity of the order of 10−5 ohm−1 cm−1 at room temperature. The relationship between the specific conductivity, σ, and the temperature was determined, and it was found that the slope of the logσ—1/T plots was equivalent to an activation energy in the range 0.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1968
1968
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…16 In addition, the concentrations of both V 4+ ions and total vanadium ions in a given volume were also raised, to which was attributed the enhanced conductivities at increasing x. 16 Our chemical shift data suggested that electron densities at each vanadium site were unevenly increased, even when both the weight densities and vanadium ion densities of the xV 2 ion concentrations, such as the VO 4 structures with at least one oxygen bonded to boron and those bonded to neighboring vanadiums, were more likely to be the vanadium oxide structures right next to V 4+ ions. However, this was not clearly elucidated in the absence of additional direct evidence to support it.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…16 In addition, the concentrations of both V 4+ ions and total vanadium ions in a given volume were also raised, to which was attributed the enhanced conductivities at increasing x. 16 Our chemical shift data suggested that electron densities at each vanadium site were unevenly increased, even when both the weight densities and vanadium ion densities of the xV 2 ion concentrations, such as the VO 4 structures with at least one oxygen bonded to boron and those bonded to neighboring vanadiums, were more likely to be the vanadium oxide structures right next to V 4+ ions. However, this was not clearly elucidated in the absence of additional direct evidence to support it.…”
Section: Resultsmentioning
confidence: 83%
“…Our NMR data suggested that Na2O converted some of the BO3 structures into BO 4 structures by donating oxygens, induced greater electric field gradients, but reduced the distortion of the electric field gradients at the boron sites of the BO3 structures. From the 51 V spectra, the VO 4 , VO 5 and VO 6 structures with all oxygens bonded to the vanadium neighbors were identified, as were the VO4 structures, with at least one oxygen bonded to boron instead of vanadium, at low Na 2 O content of y = 0.25. With increasing Na 2 O content in the glass, the vanadium sites coordinated with greater number of oxygens were more populated while less V-O-B bonding was observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…V20~ forms amorphous, vitreous compounds with several oxides like P205, TeO2, As2Oa, PbO, BaO, GeO2 [1]. Similar binary amorphous MoO 3 compounds are the systems MoO 3 -P205 [2] and MoO 3 -TeO 2.…”
Section: Introductionmentioning
confidence: 99%